Leishmania spp. infection rate and feeding patterns of sand flies (Diptera: Psychodidae) from a hyperendemic cutaneous leishmaniasis community in Panamá - Chaves, Luis Fernando (2019)
Abstract. American cutaneous leishmaniasis (ACL) is a common and important vector-borne parasitic zoonosis in Panam ´a. Here, we study Leishmania spp. infection rates and blood-feeding patterns among common sand flies in Trinidad de Las Minas, a rural community with hyperendemic ACL transmission, and where a deltamethrin fogging trial was performed. Sand flies were collected from April 2010 to June 2011 with light traps installed inside and in the peridomicile of 24 houses. We restricted our analysis to the most abundant species at the study site: Lutzomyia trapidoi, Lutzomyia gomezi, Lutzomyia panamensis, Lutzomyia triramula, and Lutzomyia dysponeta. We detected Leishmania spp. infection in sand flies by polymerase chain reaction (PCR) amplification of the internal transcribed spacer region 1 (ITS-1) in pooled females (1–10 females per pool). Host species of engorged sand flies were identified using a cytochrome b PCR. From 455 sand fly pools analyzed, 255 pools were positive for Leishmania spp., with an estimated infection rate (confidence interval) of 0.096 [0.080–0.115] before the deltamethrin fogging which slightly, but not significantly (P > 0.05), increased to 0.116 [0.098–0.136] after the deltamethrin fogging. Blood meal analysis suggested that pigs, goats, and birds were the most common sand fly blood sources, followed by humans and domestic dogs. DNA sequencing from a subsample of ITS-1 positive pools suggests that Leishmania panamensis, Leishmania naiffi, and other Leishmania spp. were the parasite species infecting the most common vectors at the study site. Our data confirm an association between sand fly species, humans, domestic dogs, and pigs and Leishmania spp. parasites in rural Panamá.